A RETROSPECTIVE STUDY OF OVARIAN TUMOURS AND TUMOUR-LIKE LESIONS - Zaman, Samina; Majid, Sarosh; Hussain, Mahvish; Chughtai, Omer; Mahboob, Javed; Chughtai, Sohail (Journal of Ayub Medical College Abbottabad, 2010)
Background: Ovaries are common site of non-neoplastic and neoplastic lesions. They can present from the neonatal period to post menopause. Most are functional in nature and resolve with minimal treatment. Objective of the study was to determine the nature of various ovarian lesions and to ascertain the frequency and distribution of the various non-neoplastic and neoplastic lesions. Methods: The study was a retrospective review of all cases of ovarian cancer, benign ovarian neoplasm and functional ovarian cysts received during Jan-Dec 2008 at Chughtai's Lahore Laboratory. The clinical data of the patients was obtained from their respective files. Results: A total of 498 different non-neoplastic and neoplastic lesions were seen during one calendar year 2008. Non-neoplastic cysts were more common (343, 68.87%) than neoplastic tumours (155, 31.12%). The commonest non-neoplastic cyst was luteal cyst followed by follicular cyst. Among the neoplastic tumours 78.70% were benign and 21.29% were malignant. Benign serous cysts were the commonest benign tumour followed by mature cystic teratoma and mucinous cyst. Serous cystadenocarcinoma was the commonest malignant tumour followed closely by endometrioid carcinoma and granulosa cell tumour. Krukenberg tumour, tumour metastatic to ovaries and non-Hodgkins lymphoma was also diagnosed during this period. Malignant germ cell tumours were seen in much younger age group followed by sex cord stromal tumours. Epithelial tumours were seen in much older age group. Conclusion: The morphologic diversity of ovarian masses poses many challenges. A specific diagnosis can usually be made by evaluating routinely stained slides but sometimes immunohistochemistry is required in difficult cases. Gross features also provide useful diagnostic clues. Keywords: Ovarian functional cysts, ovary, ovarian neoplasm